Changing impact of shocks: A time-varying proxy SVAR approach - Haroon Mumtaz; Katerina Petrova (Queen Mary University of London, School of Economics and Finance, 2018)
In this paper we extend the Bayesian Proxy VAR to incorporate time variation in the parameters. A Gibbs sampling algorithm is provided to approximate the posterior distributions of the model's parameters. Using the proposed algorithm, we estimate the time-varying effects of taxation shocks in the US and show that there is limited evidence for a structural change in the tax multiplier.
Keywords: C2; C11; E3; 330; Time-Varying parameters; Stochastic volatility; Proxy VAR; tax shocks